2023
DOI: 10.1039/d2cy01763f
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable iron-catalyzed aerobic oxidative C–C and C–O bond cleavage of a lignin model to phenol and methyl benzoate

Abstract: The selective oxidative C-C and C-O bond cleavage is of significance to the efficient ulitization of biomass and biomass-derived platform compounds. In this work, the selective oxidative cleavage of C-C...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Very recently, our group found that the selective oxidative cleavage of C−C and C−O bonds can be performed with an iron‐based catalyst (Fe−N−C) in the presence of molecular oxygen. Specifically, the β‐O‐4 lignin model compound was successfully converted to phenol and methyl benzoate in a methanol solvent, where the substrate conversion was 95.0 % and the yields of phenol and methyl benzoate were 94.9 % and 63.7 %, respectively, when the reaction was performed with the Fe−N−C‐850 catalyst at 120 °C for 4 h. The detailed investigations showed that the existence of the Fe 3 C phase in catalyst plays an important role in the aerobic oxidative cleavage of C−C and C−O bonds in the β‐O‐4 lignin model [41] . Furthermore, Hou et al [42] .…”
Section: Thermocatalytic Systems For Oxidative Valorization Of Lignin...mentioning
confidence: 98%
See 1 more Smart Citation
“…Very recently, our group found that the selective oxidative cleavage of C−C and C−O bonds can be performed with an iron‐based catalyst (Fe−N−C) in the presence of molecular oxygen. Specifically, the β‐O‐4 lignin model compound was successfully converted to phenol and methyl benzoate in a methanol solvent, where the substrate conversion was 95.0 % and the yields of phenol and methyl benzoate were 94.9 % and 63.7 %, respectively, when the reaction was performed with the Fe−N−C‐850 catalyst at 120 °C for 4 h. The detailed investigations showed that the existence of the Fe 3 C phase in catalyst plays an important role in the aerobic oxidative cleavage of C−C and C−O bonds in the β‐O‐4 lignin model [41] . Furthermore, Hou et al [42] .…”
Section: Thermocatalytic Systems For Oxidative Valorization Of Lignin...mentioning
confidence: 98%
“…Specifically, the β-O-4 lignin model compound was successfully converted to phenol and methyl benzoate in a methanol solvent, where the substrate conversion was 95.0 % and the yields of phenol and methyl benzoate were 94.9 % and 63.7 %, respectively, when the reaction was performed with the FeÀ NÀ C-850 catalyst at 120 °C for 4 h. The detailed investigations showed that the existence of the Fe 3 C phase in catalyst plays an important role in the aerobic oxidative cleavage of CÀ C and CÀ O bonds in the β-O-4 lignin model. [41] Furthermore, Hou et al [42] provided a highly active vanadium-oxygen cluster catalyst that efficiently depolymerizes lignin β-O-4 model compounds to phenol, methyl benzoate and benzoic acid in the presence of molecular oxygen. The detailed investigations showed that the presence of V 4 + and V 5 + in the catalysts is important for improving the catalytic activity of β-O-4 bond cleavage of lignin model compound.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%